Models and algorithms for cyber-physical systems - Gujrati, Sumeet (Kansas State University, 2013)
In this dissertation, we propose a cyber-physical system model, and based on this model, present algorithms for a set of distributed computing problems. Our model specifies a cyber-physical system as a combination of cyber-infrastructure, physical-infrastructure, and user behavior specification. The cyber-infrastructure is superimposed on the physical-infrastructure and continuously monitors its (physical-infrastructure's) changing state. Users operate in the physical-infrastructure and interact with the cyber-infrastructure using hand-held devices and sensors; and their behavior is specified in terms of actions they can perform (e.g., move, observe). While in traditional distributed systems, users interact solely via the underlying cyber-infrastructure, users in a cyber-physical system may interact directly with one another, access sensor data directly, and perform actions asynchronously with respect to the underlying cyber-infrastructure. These additional types of interactions have an impact on how distributed algorithms for cyber-physical systems are designed. We augment distributed mutual exclusion and predicate detection algorithms so that they can accommodate user behavior, interactions among them and the physical-infrastructure. The new algorithms have two components - one describing the behavior of the users in the physical-infrastructure and the other describing the algorithms in the cyber-infrastructure. Each combination of users' behavior and an algorithm in the cyber-infrastructure yields a different cyber-physical system algorithm. We have performed extensive simulation study of our algorithms using OMNeT++ simulation engine and Uppaal model checker. We also propose Cyber-Physical System Modeling Language (CPSML) to specify cyber-physical systems, and a centralized global state recording algorithm.
Keywords: Distributed systems; Mutual exclusion; Predicate detection; Global state recordingCyber-physical systems; Computer Science (0984)